Implementation of Similarity Check Service in Supporting Academic Integrity at Esa Unggul University Library - Nardanti, Ayudya; Irawati, Indira (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study investigates how the Turnitin-based similarity check service is implemented at Esa Unggul University Library to uphold academic integrity within higher education. The scope of this study covers an evaluation of the effectiveness of similarity check services in reducing plagiarism and enhancing academic ethics awareness within the campus environment. The main objective is to explore the perspectives of lecturers and librarians regarding the use of similarity check services, as well as the challenges and opportunities encountered during its implementation. A qualitative case study method was applied, utilizing in-depth interviews and observations involving librarians and lecturers from various faculties that have implemented similarity check policies. The key findings indicate that the similarity check service not only functions as a plagiarism detection tool but also serves as an educational medium to improve academic literacy among the academic community. Nevertheless, the library's involvement in institutional policy formulation and the strengthening of cross-unit collaboration need further development. This article contributes new insights into the importance of integrating similarity check services in fostering an honest and dignified academic culture in Indonesian higher education institutions.